Pre-Feasibility Study On The Effect Of The Gas Temperature To The Ash Separation Of Sawdust Gasification In Cyclone Gasifier. - Miskam, M.A.; Idroas, M.Y.; Alauddin, Z.A.Z.; Mustafa, K.F. (2004)
In the future, our energy system will need to be renewable and sustainable, efficient and cost-effective, convenient and safe [I], Biomass is seen as an interesting energy source for event reasons, The main reason i that bioenergy can contribute to sustainable development, Resources are often local, available and conversion into secondary energy carriers is feasible without high capital investment.